THE STUDENTS’ FEELING-BASED GRAMMAR IN RESPONDING TO TOEFL ITEMS IN GENIUS APPLICATION - Barotun Mabaroh; Ninik Suryatiningsih (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Grammar is the basis for mastering English. It is administered as a part in TOEFL as one of the English achievement standards. Due to its importance, hence the researchers focused on studying the grammar/ structure and written expression section in TOEFL. This research was also initiated based on the preliminary research which discovered many students had claimed that they tended to give answers for items in the second section based on their feelings. For understanding this phenomenon, the researchers reviewed some related literature and started collecting the data using documentation and interview. The documents were the students’ worksheets and supporting photos. While, the interview was done randomly with some purposive students. The researchers analyzed the data by listing the students’ statements on the worksheet, filtering, coding, and examining the results with logical theories. This research produced the identification of the four types of feeling, the factors, and its empirical evidence during the process of responding to TOEFL test items in Genius application. This research result could contribute to the teachers’ or the lecturers’ awareness of how to help the students recognize the standardized grammar/ structure and written expression of English, and hence they would be able to achieve a better score for the TOEFL test.